Jejunogastric intussusception in a child: A case report - Nathan Smith; Michael Morris; Barry Berch; Tamarah Westmoreland; Christopher Blewett (Elsevier, 2014)
Jejunogastric intussusception is a rare event following gastrointestinal reconstruction. We present a case report in which jejunogastric intussuception was diagnosed in a child four years after a gastrectomy with jejunogastric reconstruction for duodenal duplication. Prompt diagnosis and emergent resection of any non-viable bowel, and revision to a Roux-En-Y anastomosis with or without pexy of the Roux limb to the colon or Y-limb mesentery appear to be the appropriate treatment for this clinical entity.